Learn History Using the Rupiah Currency Utilizing Augmented Reality Technology - Saputra, Muhamad Risqi; Zakariyah, Muhammad (Postgraduate, University of Mataram, 2023)
Studying history may be very boring for students. This is what makes history learning less effective. Education is an effort aimed at developing personality and abilities for life. In education, students are individuals who are different from other people in a class. This explanation can be seen in terms of ability. Every country must have a national identityTraditional dances in Indonesia are very diverse and have their characteristics. This is because the ethnic groups in Indonesia are very numerous and diverse.Â With advances in technology, it can be used as an alternative learning solution that is more creative and efficient. Therefore, it is the basis for expanding the application of learning about the history of heroes and dances on rupiah banknotes using the Augmented Reality Marker Training method. It is important to have a useful means of displaying and introducing each national hero featured on a particular currency By utilizing these technological Advances we can visualize images more realistically and in real-time, this is what will attract the interest of users, especially students, to use this application as a medium for learning the history of heroes and introducing regional dances found on the rupiah currency